Prescrição virtual: uma realidade no direito penal brasileiro: estudo sobre o reconhecimento antecipado da prescrição retroativa e o interesse de agir no direito pátrio - Romão, César Eduardo Lavoura (2009)
The present work aims at to deepen the study of virtual or anticipated lapse, analyzing its use for the Brazilian Judiciary Power, mainly for the magistrates of lower court. This controversial institute comes being understood as cause of elimination of the interest of action in the criminal proceeding whenever evidenced the possibility of decrements of the punitive lapsing pretension in the retroactive modality, early in the process, even before of the act of receiving the denunciation or of pronounced the sentence, leading in consideration a hypothetical penalty surveyed by the refined circumstances until that moment. For times, after a long procedural proceeding with an intricate probatory instruction, the magistrate is obliged to pronounce the sentence, convicted the defendant and, immediately afterwards, to recognize the extinguishing of the punshability for the retroactive lapsing of the punitive pretension, playing for the thin one, all the developed intellective work in the course of the process and, mainly, at the moment of the elaboration of the condemnatory decree. It is accurately in this scene, and on behalf of the procedural economy and of the effective and coherent search of the application of the penalties, that the virtual lapsing demonstrates to its force and utility. This because it searches to move away from the Judiciary Power useless processes, that will not have resulted beneficial, contributing, only, to generate, unnecessary, more service and, consequently, greater slowness in the procedural proceeding. For the understanding of subject so controversial, surrounded of favorable and contrary arguments, one searched to analyze, in this research, in order to select its validity before the legal system, each one of the arguments advantages and against the institute. First, the consistent ones in the absence of action right; in the criminal proceeding as a pledge of the defendant and not as sanction; in the beginning of the judgment quickly; in the uselessness of the judgment of the prescribed process; e in the similarity of the decision that receives the lapsing with the acquittal. The seconds, contrary to its application, in the pretense breaking the beginning of the legality; the beginning of the innocence presumption; to the obligatoriness of the criminal action; to the possibility of amendment of complain (mutatio libelli); and to the condition of the victim in the process. However, before the ingression in the object of the controversy, there was the analysis of related institutions, such as the right to punish, the purposes of punishment, the criminal action and the proper lapsing, as extinctive cause of ius puniendi